Genomic and Transcriptomic Insight of Giant Sclerotium Formation of Wood-Decay Fungi - Cao, Shuo; Yang, Yang; Bi, Guiqi; Nelson, David; Hu, Sheng; Makunga, Nokwanda Pearl; Yu, Bin; Liu, Xin; Li, Xiaohua; Hu, Xuebo (Frontiers in Microbiology, 2021)
Many fungi form persistent and dormant sclerotia with compact hardened mycelia during unfavorable circumstances. While most of these sclerotia are small in size, Wolfiporia cocos, a wood-decay fungus, grows into giant sclerotia, which are mainly composed of polysaccharides of linear (1→3)-β-D-glucans. To explore the underlying mechanism of converting sophisticated wood polysaccharides for biosynthesis of highly homogenized glucans in W. cocos, we sequenced and assembled the genome of a cultivated W. cocos strain (WCLT) in China. The 62-Mb haploid genome contains 44.2% repeat sequences, of which, 48.0% are transposable elements (TEs). Contrary to the genome of W. cocos from North America, WCLT has independently undergone a partial genome duplication (PGD) event. The large-scale TE insertion and PGD occurrence overlapped with an archeological Pleistocene stage of low oxygen and high temperature, and these stresses might have induced the differences in sclerotium due to geographical distribution. The wood decomposition enzymes, as well as sclerotium-regulator kinases, aquaporins, and highly expanded gene families such as NAD-related families, together with actively expressed 1,3-β-glucan synthase for sclerotium polysaccharides, all have contributed to the sclerotium formation and expansion. This study shall inspire further exploration on how fungi convert wood into simple glucans in the sclerotium of W. cocos.